An adaptable and ISP-friendly multicast overlay network - Sampaio, Andre (2019)
Multicast is a group communication paradigm which aims at reducing, as much as possible, the amount of data generated into the network. Thus, IP Multicast presents itself as a technology that allows data to be distributed in such a way that the least amount of replicas of the same packet is placed into the network. However, the limited deployment of IP level Multicast protocols has lead to new approaches, in the application-level, implementing multicast using end systems and not routers. This concept has resulted in different approaches denominated as Application-Layer Multicast (ALM) or Overlay Multicast based systems. In this context, this work presents and analyzes an overlay multicast system envisioned to be highly reconfigurable and adaptable to different usability contexts. Such system versatility is not only present in the capability to construct distinct multicast distribution trees, but also in the integration of several advanced Traffic Engineering mechanisms based on collaborative efforts between the overlay and the Internet Service Provider (ISP) levels. Results from the proposed overlay system and associated mechanisms are obtained using a real system implementation which has been tested in a network emulation tool, with the experimental scenarios encompassing both single and multiple Autonomous Systems (AS).